PISCIAN CESTODE OF BUNDELKHAND REGION OF UTTAR PRADESH, SENGA JHANSIENSIS N. SP. (CESTODA : PTYCHOBOTHRIIDAE) FROM MASTACEMBELUS ARMATUS (LACEPEDE) - MATHUR, NOOPUR; SRIVASTAV, A.K.; RANI, DAISY (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
The present paper deals with a new species belonging to genus Senga. Dollfus (1934) established genus Senga for the worms collected Betta splendens with S. besnardi as type specimens. Many species of Senga have also been described from Ophiocephalus, Mastacembelus and Channa species. The cestodes collected were from the intestine of Mastacembelus armatus. They were fixed in 5% formaline and stained with Mayer's haemalum. The descriptions are based on five specimens and all measurements in mm.